Micromechanical modeling of short-fiber reinforced composites - Müller, Viktor (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2016)
This work is focused on the prediction of elastic behavior of short-fiber reinforced composites by mean-field homogenization methods, which account for experimentally determined and artificially constructed microstructure data in discrete and averaged form. The predictions are compared with experimental measurements and a full-field voxel-based approach. It is investigated, whether the second-order orientation tensor delivers a sufficient microstructure description for such predictions.